Analisis Pengaruh Work From Home dan Disiplin Kerja Terhadap Kinerja Melalui Motivasi Pada Karyawan Bagian Administrasi PT. Asta Ilmu Jakarta - Fatmawaty Fransiska Br Munte; Theresia Pradiani; Fathorrahman Fathorrahman (Jurnal Indonesia Sosial Sains, 2023)
Good human resource management will produce reliable employees with optimal performance which will support the company goals achievement. Employee performance needs to get absolute attention by company management because performance will affect the company's development and ability to survive in dynamic global competition. PT. ASTA Ilmu is a company established with a vision and mission to build high quality Indonesian human resources (HR) through education. This research is done to determine the effect of WFH and work discipline on the performance of employees in the administrative division of PT. ASTA Ilmu through motivation as an intervening variable. The sampling method is saturated sampling method, in which a total of 33 administrative employees at PT. ASTA Ilmu was used as a sample in this study. The research results show that the variables of work discipline and motivation have a significant effect on the performance of employees in the administrative division of PT. ASTA Ilmu, the WFH variable has no effect on performance and motivation, the motivation variable is able to mediate the WFH and work discipline on the performance of employees in the administrative division of PT. ASTA Ilmu